Kesenjangan Harapan Antara Nasabah dan Manajemen terhadap Penyampaian Informasi Keuangan dan Non Keuangan Bank Syariah - Yaya, Rizal; Abdurahim, Ahim; Nugraha, Danang Aji (Universitas Muhammadiyah Yogyakarta, Indonesia, 2007)
The use of revenue sharing between depositors and the bank in the operation of Islamic Banks, has created an agency problem. Regarding with this problem, Banks should provide both financial and non financial information for the depositors. This research tries to find out the possibility of the existence of expectation gap in the information provided by banks as the provider of information to the depositors as the user of the information. Based on assimetry information theory, depositors as a party with less information, would demand more information to the banks. However for some reasons, banks might restrict the information provided to the depositors. One hundred ninety-two depositors and one hundred thirty-eight staffs of Islamic banks in Yogyakarta and Surakarta has been surveyed with questionnaire. This research used independent sample t-test in analyzing the expectation gap of the two groups. The result shows that (1) the user of information have significantly less expectation than the provider of financial information, (2) there is no expectation gap between the user and the provider of banks’ information in non financial information